Arsenic trioxide induces programmed cell death through stimulation of ER stress and inhibition of the ubiquitin–proteasome system in human sarcoma cells. Issue 2 (28th January 2015) - Chiu, Hui-Wen; Tseng, Yin-Chiu; Hsu, Yung-Ho; Lin, Yuh-Feng; Foo, Ning-Ping; Guo, How-Ran; Wang, Ying-Jan
Highlights: Arsenic trioxide (ATO) caused cell death in human osteosarcoma and fibrosarcoma cells. The types of cell death that were induced by ATO were primarily autophagy and apoptosis. ATO activated p38, JNK and AMPK and inhibited the Akt/mTOR signaling pathways. ATO induced endoplasmic reticulum stress and suppressed proteasome activation in sarcoma cells. The combination treatment of ATO and a proteasome inhibitor resulted in synergistic cytotoxicity. Abstract: Sarcoma is a rare form of cancer that differs from the much more common carcinomas because it occurs in a distinct type of tissue. Many patients of sarcoma have poor response to chemotherapy and an increased risk for local recurrence. Arsenic trioxide (ATO) is used to treat certain types of leukemia. Recently, data have revealed that ATO induces sarcoma cell death in several types of solid tumor cell lines. In the present study, we investigated whether ATO induces cancer cell death and elucidated the underlying anti-cancer mechanisms. Our results showed that ATO caused concentration- and time-dependent cell death in human osteosarcoma and fibrosarcoma cells. The types of cell death that were induced by ATO were primarily autophagy and apoptosis. Furthermore, ATO activated p38, JNK and AMPK and inhibited the Akt/mTOR signaling pathways. Specifically, we found that ATO induced endoplasmic reticulum (ER) stress and suppressed proteasome activation in two types of sarcoma cell lines. However, the level of proteasome inhibition in osteosarcoma cells was lower than in fibrosarcoma cells. Thus, we used combined treatment with ATO and a proteasome inhibitor to examine the antitumor activity in fibrosarcoma cells. The data indicated showed that the combination treatment of ATO and MG132 (a proteasome inhibitor) resulted in synergistic cytotoxicity. In a fibrosarcoma xenograft mouse model, the combined treatment significantly reduced tumor progression. Immunohistochemical studies revealed that combined treatment induced autophagy and apoptosis. In summary, our results suggest a potential clinical application of ATO in sarcoma therapy and that combined treatment with a proteasome inhibitor can increase the therapeutic efficacy.